Catalytic gasification of empty fruit bunch for enhanced production of hydrogen rich fuel gas - Al-Obaidi, Mohammed Mahmoud Ahmad; Ali, Salmiaton; Wan Ab. Karim Ghani, Wan Azlina; Mohd Salleh, Mohamad Amran; Omar, Rozita; Yap, Taufiq Yun Hin; Ahmadun, Fakhru'l-Razi (Universiti Putra Malaysia Press, 2012)
Oil palm is widely grown in Malaysia. There has been interest in the utilization of oil palm biomass for production of environmental friendly biofuels. The gasification of empty fruit bunches (EFB), a waste of the palm oil industry, was investigated in this study to effectively and economically convert low value and highly distribution solid biomass to a uniform gaseous mixture mainly hydrogen (H2). The effects of temperature, equivalence ratio (ER) and catalyst adding on the yields and distribution of hydrogen rich gas products were also investigated. The main gas species generated, as identified by GC, were H2, CO, CO2, CH4and trace amounts of C2 H4 and C2 H6. With temperature increasing from 700 to 1000°C, the total gas yield was enhanced greatly and reached the maximum value (~ 90 wt. %) at 1000°C with a big portion of H2(38.02 vol. %) and CO (36.36 vol. %). Equivalence ratio (ER) showed a significant influence on the upgrading of hydrogen production and product distribution. The optimum ER (0.25) was found to attain a higher H2 yield (27.42 vol. %) at 850°C. The effect of adding catalysts (Malaysian dolomite1, P1), Malaysian dolomite2 (GML), NaOH, NaCl, CaO, ZnO, NiO) as a primary catalyst on gas product yield was investigated, and it was found that adding dolomite showed the greatest effect with the maximum H2 yield achieved (28.18 vol.%) at 850°C.